1970
DOI: 10.1039/c2970000178a
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of endocrocin, endocrocin-9-anthrone, and related compounds

Abstract: Endocrocin-9-anthrone and endocrocin, the biogenetic precursors of emodin-type anthraquinones, have been synthesized by a method easily adaptable to the synthesis of radioactively labelled compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We found that overexpression of the encA transcript resulted in higher transcript levels of encA-D and higher production of endocrocin. We discuss a model of the enc cluster as one evolutionary origin of fungal anthraquinones derived from a nonreducing polyketide synthase and a discrete metallo-␤-lactamase-type thioesterase.T he anthraquinone endocrocin was first described in 1935 from the lichen Nephromopsis endocrocea and since has been isolated from various fungi (16,26,30,37), insects (22), and plants (17). Endocrocin and related anthraquinones are noted for their industrial uses as dyes, food additives, components of paper making, and cosmetics (18) as well as for their medicinal uses, including as laxative, anti-inflammatory, and antitumor agents (17,19).…”
mentioning
confidence: 99%
“…We found that overexpression of the encA transcript resulted in higher transcript levels of encA-D and higher production of endocrocin. We discuss a model of the enc cluster as one evolutionary origin of fungal anthraquinones derived from a nonreducing polyketide synthase and a discrete metallo-␤-lactamase-type thioesterase.T he anthraquinone endocrocin was first described in 1935 from the lichen Nephromopsis endocrocea and since has been isolated from various fungi (16,26,30,37), insects (22), and plants (17). Endocrocin and related anthraquinones are noted for their industrial uses as dyes, food additives, components of paper making, and cosmetics (18) as well as for their medicinal uses, including as laxative, anti-inflammatory, and antitumor agents (17,19).…”
mentioning
confidence: 99%
“…The aptC deletion mutant did not produce any major compound detectable at a UV wavelength of 254 nm (see Fig. S3 in the supplemental material) since endocrocin-9-anthrone is known to be unstable in solution (22) and probably decomposed during the extraction process.…”
Section: Discussionmentioning
confidence: 99%